Molecular and Cellular Characterization of SIRT1 Allosteric Activators - Schultz, Michael B. (Methods Mol Biol, 2019)
SIRT1 is an NAD(+)-dependent lysine deacetylase that promotes healthy aging and longevity in diverse organisms. Small molecule allosteric activators of SIRT1 such as resveratrol and SRT2104 directly bind to the N-terminus of SIRT1 and lower the K(m) for the protein substrate. In rodents, sirtuin-activating compounds (STACs) protect from age-related diseases and extend life span. In human clinical trials, STACs have a high safety profile and anti-inflammatory activities. Here, we describe methods for identifying and characterizing STACs, including production of recombinant protein, in vitro assays with recombinant protein, and cellular assays based on mitochondrial dynamics. The methods described in this chapter will facilitate this discovery of improved STACs, natural and synthetic, in the pursuit of interventions to treat age-related diseases.